Post-fire succession of pseudo-taiga larch forest in the Tarvagatai Mountain range, Mongolia - M. Undraa; Sergey N. Bazha; B. Oyunsanaa; Ch. Dorjsuren (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2024)
Understanding post-fire recovery and succession is crucial for determining the forest’s further reestablishment rate and development tendency, facilitating the restoration and protection of degraded forests, and planning post-fire forest management. The main aim of this study was to evaluate forest regeneration and reveal the tendency of plant succession after large-scale fire in the Tarvagatai Mountain range, Central Khangai, Mongolia. The monitoring study on post-fire plant succession and regeneration in the forbs-Rhytidium mosses pseudotaiga larch forests was conducted on permanent sample plots from 2007 to 2021 in the forest sites, which were damaged by severe fires in 1996 and 2002. Our results indicated that burned forest was regenerated sufficiently through the several serial stages of post-fire successions as fireweed (Chamaenerion angustifolium) community (up to 5 years after fire), fireweed-bonfire moss (Funaria hygrometrica) community (from 6 to 10 years), forbs community (11-16 years), grass-forbs young larch forest (17-25 years). Species numbers gradually increased with time in the forest affected by fires, whereas they rose drastically in the forest damaged by fire and livestock browsing due to the increase of ruderal species. In spite of the long recovery period, the post-fire similarity indexes of species composition and coenotic percentage compared with the control forest were relatively low, indicating a slow pre-fire vegetation recovery.